Characterization of the complete mitogenomes of the Asian Paradise Flycatcher Terpsiphone paradisi (Monarchidae) and phylogenetic analysis. Issue 3 (2nd July 2020) - Hou, Xiang; Yuan, Hao; Du, Xiao-Juan; Gong, Hui-Sheng; Chang, Gang; Yang, Chao; Wang, Yan
Abstract: The mitogenome of Terpsiphone paradisi is 16, 951 bp in length and consists of 22 tRNA genes, two rRNA genes, 13 protein-coding genes and one control region. The nucleotide frequencies of As, Ts, Cs, Gs of the mitogenome is 31.0%, 24.7%, 29.8% and 14.5%, respectively. All PCGs start with typical ATN codon with the exception of COI genes, which use GTG as the initiation codon, and Most PCGs end with AGG, AGA, TAA, or TAG, except for COII, COIII and ND4, which terminated with T instead. Phylogenetic analysis indicated that genetic distances of T. paradisi and Terpsiphone atrocaudata was closer than other species.